The Electropolishing of C-Steel in Orthophosphoric Acid Containing Methanolic Plant Extract - Asia A. Taha; Fatma M. Abouzeid; Mohamed M. Elsadek; Yasmeen M. Othman (Journal of Chemistry)
Plant extracts have been regarded as “green” alternatives as additives for metal electropolishing improvement. Therefore, understanding the electrochemical properties and the reaction mechanisms of the electroactive compounds from the plant extracts is necessary to further explore the mechanism and application of the plant extract-based additives for metal dissolution. The C-steel electropolishing behavior in orthophosphoric acid using the galvanostatic polarization and weight loss methods was ascertained. This was inspected via anode potential-limiting current relationship measurement and comparison in a solution of regularly mounting concentrations (from 50 to 1800 ppm of methanolic marjoram, coriander seeds, chamomile, and guava leaves extract), and the influence of temperature on the dissolution kinetics was investigated. Surface morphologies, roughness, and reflection of investigated specimens were inspected with a scanning electron microscope (SEM), profilometry, and Vis-IR spectroscopy. Addition of methanolic plant extract to the electropolishing solution results in a lower limiting current. Retardation percentage gained from mass loss measurement is comparable with those obtained from measurements of galvanostatic polarization. Addition of 500 ppm of marjoram, coriander, chamomile, and guava leaves increases the degree of surface brightness and reflectance to 64.9, 56.59, 27, and 24.5, respectively, relative to electropolishing electrolyte-free solution 16. The roughness (Ra) decreased from 2.7 μm to 0.52 μm without addition of any material. Ra values are 0.28, 0.23, 0.21, and 0.17 μm in the presence of guava leaves, chamomile, coriander seeds, and marjoram.